The Relationship Between The Economic Conditions Of Millennial Parents And The Learning Motivation Of Early Childhood - Maria Qori'ah; Viena Wanidha Andriani; Imam Wahyono; Riris Wahyuningsih; Ria Octa Viana; Risma Nurfaiqotul Himah (Journal of Educational Studies, 2026)
In today's society, millennial parents face real challenges in the form of soaring preschool costs and increasingly demanding educational facilities for children. This uncertain economic situation creates an urgent need to understand how family financial stability affects children's mental readiness and motivation to learn during their early developmental stages. This study aims to analyze the relationship between the economic conditions of millennial parents and the learning motivation of 5-6-year-old children at Muslimat Khadijah Kindergarten 157 Rogojampi. Referring to Lawrence W. Green's theory, this study positions economic conditions as an enabling factor that determines the accessibility of educational facilities, while the values ??held by parents act as a predisposing factor. The research method used was a quantitative correlational method with a sample of 90 participants. Data were collected through questionnaires, classroom observations, and documentation, which were then analyzed using the Pearson Product-Moment correlation test. The results of the descriptive analysis show that the majority of families are in the middle (42.22%) and low (38.89%) economic categories, but children's learning motivation remains stable with an average score of 70.1. The results of the hypothesis test yielded a correlation coefficient of r = 0.714 with a significance value of 0.000 < 0.05, indicating a strong and significant positive relationship between the two variables. This finding reveals that millennial parents allocate their budget strategically by reducing tertiary expenses to prioritize essential educational needs at home. The study's conclusion confirms that family economic stability is closely related to the direction of children's motivational development. The balance between targeted financial support and intensive parenting patterns is the main key to building children's enthusiasm for learning amidst the increasingly competitive demands of life.